"Affective News" and Attitudes: A Multi-Topic Experiment of Attitude Impacts From Political News and Fiction. (December 2021) - Knobloch-Westerwick, Silvia; Robinson, Melissa; Frazer, Rebecca; Schutz, Emily
Popular entertainment often involves political messages, and entertainment elements are now commonly used in politics coverage. This study examines how suspense drives impacts of political entertainment media content on attitudes, building on the "affective news" extended model. Hypotheses were tested with four texts on controversial political issues (within-subjects), presented in a linear or inverted-pyramid structure and either as news or fiction . The resulting 2 × 2 × 3 × 4 online experiment ( N = 227) showed that linear texts produced greater suspense and attitude change than inverted-pyramid texts. Suspense mediated attitude impacts. Both news and fiction versions influenced attitudes, with impacts still detectable 1 day after exposure.